Enhancing empathy among humanitarian workers through Project MIRACLE: Development and initial validation of the Helpful Responses to Refugees Questionnaire - Potocky, Miriam; Guskovict, Kristen L. (Torture Journal, 2018)
Background: Empathy is an important tool needed for service providers working with people who have experienced trauma, such as refugees and torture survivors. However, the high caseloads, rigorous deadlines, and overwhelming circumstances under which humanitarian workers typically operate often make it challenging to employ empathy. The Helpful Responses to Refugees Questionnaire (HRRQ) was developed to measure empathetic responsiveness, a core skill of Motivational Interviewing, among service providers working with refugees, including torture survivors. Methods: The HRRQ was adapted specifically for measuring empathy in refugee contexts, including among asylum-seekers and torture survivors. Face validity and content validity were established by a panel of refugee resettlement experts prior to administration. The instrument was then administered via an online survey to a national sample of refugee service providers (valid N=90). Findings: The HRRQ demonstrated good psychometric properties. Interpretation: The HRRQ has several potential applications for work with refugees, including torture survivors. It could be used as a supervisory tool to assess service providers’ skills in this area and provide feedback for improvement if needed. It could also be used as a screening tool for hiring new staff as part of a comprehensive screening and selection process. Finally, it may be used as a pretest-posttest to evaluate the impact of staff training in motivational interviewing. Limitations of this study and implications for future research are discussed.